Right to Freedom of Religion and Right to Clean Environment: A case of Bagmati River, Pashupatinath Temple - Yonzon, Dia Maijadh; K.C., Ojaswi (Kathmandu School of Law Review, 2019)
This research deals with two fundamental rights listed in the Constitution of Nepal, 2015; the Right to freedom of religion and the Right to clean environment with a special reference to the Bagmati River and riverbank in Pashupatinath Temple. The aim of the research is to visualize a clean river while keeping in mind the continuation of centuries-old traditions. The research explores the question of whether the religious practices performed in the river are destructible to the river ecosystem or not. It further tries to see the stance of state regarding its approach to finding the middle ground between the two different fundamental rights. The researchers have assessed this dimension through the study of ritual performance in the banks of Bagmati River, state policy and citizen’s attitude regarding this issue. Bagmati River is considered as a holiest of holy by followers of Hinduism. It provides a sample to understand the significant role played by other Hindu temples and their river banks located in the territory of Nepal in determining the river’ s purposes along with the sustainability of the river and its tributaries.